Impact of Asymmetric Information in Islamic Financial contract: An Empirical Analysis - Zafar, Sajjad Hussain; Siddiqui, Danish A (European Journal of Islamic Finance, 2019)
A primary source of asymmetric information arises from banks’ uncertainty about borrowers’ Creditworthiness. This can generate two types of barriers to efficient credit allocation in the loan market: ad-verse selection in the likelihood of repayment and moral hazard in the riskiness of firms’ business decisions, also affecting repayment. This study investigated the consequences of asymmetric information on Islamic financial contracts in the Pakistani market for small and medium enterprise (SME) business lines of credit. Islamic bank’s main financial contracts were discuss the two of them which are Istisna and Murabah .The methods of’ T test’ was conducted to ascertain the difference in means of both forms of financing, whereas Multiple Regression Analysis using panel data to assess the relationship of critical variables with Disbursed amount, profit rate, spread, tenor. Data of three year i.e. from 2016 to2018 of 35 firms, with 105 number of observations having istisna and murabah contract, were taken. The results suggested that both the means of murabah and istisna financing are significantly different in major performance indicators, implicating companies that have taken these two financing have performed differently. Secondly, in most of the ratio that mattered like efficiency and profitability, murabah based financing have yielded more efficient results and better performed as compared to istisna.